A pilot cross-sectional study of non-communicable diseases in TB household contacts - Y. Hamada; A. Lugendo; T. Ntshiqa; G. Kubeka; J.M. Lalashowi; S. Mwastaula; K. Ntshamane; I. Sabi; S. Wilson; A. Copas; K. Velen; N.E. Ntinginya; et al. (IJTLD Open)
BACKGROUND: Data on the prevalence of non-communicable diseases (NCDs) in TB household contacts (HHCs) are limited, yet important to inform integrated screening and care for NCD within contact investigations. It is also unclear if screening these contacts reveals more people with NCDs than individuals in the same neighbourhood. METHOD: We conducted a pilot cross-sectional study in South Africa and Tanzania, enrolling adult HHCs of TB and individuals in neighbourhood households (controls). We inquired about known NCD and systematically measured blood pressure, and tested for spot blood glucose and haemoglobin A1c. RESULTS: We enrolled 203 adult contacts of 111 persons with TB and 160 controls. Among contacts, respectively 12.2% (95% CI 8.3–17.6) and 39.7% (95% CI 33.1–46.7) had diabetes and hypertension, compared to 14.1% (95% CI 9.2–21.0) and 44.7% (95% CI 36.9–52.7) among controls. More than half of NCDs were newly identified. We did not find a significant difference in the prevalence of at least one NCD between the two groups (OR 0.85, 95% CI 0.50–1.45, adjusted for age and sex). CONCLUSIONS: We found a high prevalence of undiagnosed NCDs among contacts, suggesting a potential benefit of integrating NCD screening and care within contact investigations. Screening in the same community might similarly find undiagnosed NCDs.